Monitoring Pencegahan Stunting Pada Anak Di Bawah Usia 5 Tahun dengan GROWUP - Muhammad Sahidal; Yuliarman Saragih; Arnisa Stefanie (Jurnal Ilmiah Wahana Pendidikan, 2023)
In Indonesia, the problem of stunting is still a serious problem, as evidenced by the existence of the 2020-2024 National Medium-Term Development Plan, namely the National Strategy to Accelerate the Reduction of Stunting Rates through Presidential Regulation Number 72 of 2021. The issue of stunting is a national issue because it can threaten human resources that will become the next generation Indonesian nation. Nutrition interventions must be carried out to narrow the possibility of stunting in children under 5 years of age. GrowUp is present as a platform that functions to monitor the occurrence of Nutrition Interventions. The 3 main features of GrowUp are data collection on important matters related to stunting, such as age, height, weight, and zScore calculations, socialization features for educating parents starting from the need to prevent stunting since pregnancy, reminder features to remind parents about immunization and providing adequate nutrition in the food of his baby. GrowUp is a Web Based Application that uses Software Code Editor tools, namely Visual Studio Code, Git, Xampp, Composer and also uses the PHP Programming Language, HTML/CSS, mySql, Javascript. The framework used is Laravel and for the Framework Interface it uses Boostrap